Barriers to health access among Filipinos in Spain: results from interviews with immigrants - Melynn Grace Parcon; Sara Darias-Curvo; Cristo Manuel Marrero-González (Frontiers in Human Dynamics)
IntroductionImmigrants across the globe face significant healthcare access barriers. Beyond the fundamental right to health, the well-being of immigrant populations directly impacts the overall health of the host country. Despite the presence of over 200,000 Filipino immigrants in Spain, existing literature on their health and well-being remains limited.MethodsA face-to-face, interview-based, qualitative study consisting of 8 individual interviews (7 women and 1 man) and 2 focus groups: women (7) and men (5) were carried out. Participants were recruited through convenience and snowball sampling. Data was analyzed thematically.ResultsBarriers to healthcare encountered by immigrants were divided into 3 subthemes: socio-cultural (health-seeking behavior, diet, endures suffering), socio-economic (family dynamics, working conditions, education), and healthcare services related (negative healthcare experiences). Filipino community organizations and faith helped immigrants manage stress.ConclusionTo improve healthcare access, health literacy and integration must be promoted. Before coming to Spain, immigrants must be equipped with cultural and linguistic knowledge to mitigate work stress and facilitate assimilation. Structural changes must be promoted by both countries such as streamlining the immigration processes to reduce economic burden and ensuring a healthy workplace for immigrants.